Discursive evaluation in a distributed learning community - Svensson, Lars (Australasian Journal of Educational Technology, 2002)
This paper describes a distance education project where a threaded discussion board was used for interaction amongst students and teachers. The experiences from the first year of the project shows that such a forum can be an important complement to other evaluative resources in order to monitor student's expectations and experiences. Furthermore, it is argued that discursive evaluations can establish a learning community with shared norms and forms of communication and collaboration. Vital properties of the discussion board are that it is continuous, online, public, asynchronous and auto-structuring.